2014
DOI: 10.1017/s0033291714002360
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of bilateral repetitive transcranial magnetic stimulation for negative symptoms of schizophrenia: results of a multicenter double-blind randomized controlled trial

Abstract: Bilateral 10 Hz prefrontal rTMS reduced negative symptoms, as measured with the SANS. More studies are needed to investigate optimal parameters for rTMS, the cognitive effects and the neural basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 73 publications
(89 reference statements)
3
56
1
2
Order By: Relevance
“…In our review, we came across a single study which had a follow-up period comparable to ours. Dlabac-Delange and colleagues (2015) found sustained improvement in SANS scores over a period of 3 months with 10 Hz, total of 30000 pulses to each hemisphere [13]. Similarly, the favourable effects of rTMS in our study also seemed to be sustained over 4 months of follow-up after the intervention.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In our review, we came across a single study which had a follow-up period comparable to ours. Dlabac-Delange and colleagues (2015) found sustained improvement in SANS scores over a period of 3 months with 10 Hz, total of 30000 pulses to each hemisphere [13]. Similarly, the favourable effects of rTMS in our study also seemed to be sustained over 4 months of follow-up after the intervention.…”
Section: Discussionsupporting
confidence: 84%
“…An important advantage in our study was the use of sham coil. Majority of the studies use the intervention coil as sham by tilting it to 90 [12,13,31]. This method has been found to induce at least some voltage in the brain [34],whereas, a sham coil is devoid of this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with a double-blind design that had cognitive measures as secondary outcomes could principally not overserve a beneficial effect of active stimulation compared to sham stimulation. 9,22,26,27,30,34,36,41,45 Other studies 33,35,37,50 indicate a potential benefit of active neurostimulation applied to the DLPFC on verbal memory, source monitoring, cognitive flexibility, or verbal fluency, whereas the aforementioned negative studies failed to show a benefit in the same or related domains. Interestingly, one study using high-frequency rTMS applied to the left DLPFC focused on the safety effect of frontal neurostimulation and did not reveal any potential harmful effect on cognition.…”
Section: Results Of Individual Studies (Outcomes)mentioning
confidence: 99%
“…The benefits persisted up to 24 weeks [47]. A smaller (n=32) recent study utilizing bilateral TMS also found improvement in SANS scores that lasted up to three months [48]. To date, four meta-analyses have been performed regarding the effect of TMS on negative symptoms and have consistently found a moderate effect size.…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%